Determinants of effective telecommuting practices among family business companies in China - Yunzheng, Lu (2023)
The transformation of the field of human resource management is mainly through telecommuting, which acts as a trigger that changes the traditional concept of work. This is because of the impact of the technology boom and the issue of COVID 19 which leads to new work practices through the internet. This study explores telecommuting work practices by focusing on three important factors namely technology and equipment, communication and work environment. Through a qualitative study by interviewing nine managers from three companies who have experience practicing telecommuting in their employment affairs. The findings confirm the symbiotic relationship between technology quality and telecommuting success, emphasizing adaptability and accessibility. Effective communication emerges as the basis for bridging geographical divides, with clarity, regularity, and team culture playing a key role. The impact of the work environment extends beyond physical considerations, emphasizing the need for a balance between autonomy and organizational support. The practical implications emphasize strategic investment in technology, a comprehensive communication strategy, and the creation of a supportive work environment. This study also contributes to new human resource management practices by providing a basis for understanding the evolving nature of telecommuting, empowering organizations to make informed decisions in shaping a flexible and productive workforce.